2019
DOI: 10.1080/13651501.2019.1687724
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive findings in young adults with binge eating disorder

Abstract: Objectives: Binge-eating disorder (BED) has been associated with cognitive impairment, including on measures of impulsivity, but it is not clear in prior literature whether these deficits may have been associated with obesity, rather than BED per se. Impulsivity may play a role in predisposing people towards BED as well as in the chronicity of symptoms. The aim of this study was to examine cognitive functions between BED and healthy controls matched for age, gender, and body mass indices. Methods: Individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…Depressive symptoms were correlated with overall neuropsychological inefficiencies BED group: psychiatric disorder not specified (n = 10) Cognitive Flexibility : WCST (perseverative errors), TMT (B-A). Working Memory : BDS, FDS Inhibition : BRIEF-A (behavioral index), Stroop test (trial3/trial1) Others : RCFT (central coherence), IGT (total net score) Duchesne et al, 2010 38(29) 38(34) 34.35 36.24 _ _ Whole sample: specific phobia (12%), generalized anxiety disorder (10%), dysthymic disorder (6%), panic disorder (9%), agoraphobia (4%), social phobia (5%), alcohol abuse/dependence (3%), posttraumatic stress disorder (3%), premenstrual dysphoric disorder (2%), obsessive–compulsive disorder (2%), and others (1%) Cognitive Flexibility : WCST (perseverative errors), TMT-B, BADS Rule Shift Cards (n° errors) Working Memory : BDS, FDS Inhibition : Stroop test (correct answers, color-word trial) Others : BADS Action Program Test (n° stages completed), BADS Zoo Map Test (trial 1, n° errors), BADS Modified Six Elements Eneva et al, 2017 55(55) 77(77) 32.1 28.4 _ Presence of psychiatric disorders did not significantly correlate with performance on any executive function measures BED group: mood disorder (n = 5), anxiety (n = 10) Cognitive Flexibility : DKEFS-trail making switching, NIH dimensional change card sort Working Memory : NIH working memory Inhibition : DKEFS color word interference inhibition, NIH flanker inhibitory control Others : DKEFS verbal fluency, design fluency and tower achievement Grant & Chamberlain, 2020 17(11) 17(11) 24.62 32.63 HAM-D, HAM-A BED group reported subclinical levels of depression and anxiety. No further control BED group: agoraphobia (n = 2), social phobia (n = 1), cannabis use disorder (n = 1), antisocial personality disorder (n = 1) Cognitive Flexibility : IED (total errors, adjusted for stages not completed) Working Memory : One Touch Stockings of Cambridge task (problems solved on first choice), Spatial Working Memory Task* (total errors) Inhibition : SST (stop-signal reaction time) Others : CGT (quality of decision making) Kittel et al, 2017 22(18) 44(36) 14.99 85.66* BDI-II S-Diff in depression sym...…”
Section: Resultsmentioning
confidence: 99%
“…Depressive symptoms were correlated with overall neuropsychological inefficiencies BED group: psychiatric disorder not specified (n = 10) Cognitive Flexibility : WCST (perseverative errors), TMT (B-A). Working Memory : BDS, FDS Inhibition : BRIEF-A (behavioral index), Stroop test (trial3/trial1) Others : RCFT (central coherence), IGT (total net score) Duchesne et al, 2010 38(29) 38(34) 34.35 36.24 _ _ Whole sample: specific phobia (12%), generalized anxiety disorder (10%), dysthymic disorder (6%), panic disorder (9%), agoraphobia (4%), social phobia (5%), alcohol abuse/dependence (3%), posttraumatic stress disorder (3%), premenstrual dysphoric disorder (2%), obsessive–compulsive disorder (2%), and others (1%) Cognitive Flexibility : WCST (perseverative errors), TMT-B, BADS Rule Shift Cards (n° errors) Working Memory : BDS, FDS Inhibition : Stroop test (correct answers, color-word trial) Others : BADS Action Program Test (n° stages completed), BADS Zoo Map Test (trial 1, n° errors), BADS Modified Six Elements Eneva et al, 2017 55(55) 77(77) 32.1 28.4 _ Presence of psychiatric disorders did not significantly correlate with performance on any executive function measures BED group: mood disorder (n = 5), anxiety (n = 10) Cognitive Flexibility : DKEFS-trail making switching, NIH dimensional change card sort Working Memory : NIH working memory Inhibition : DKEFS color word interference inhibition, NIH flanker inhibitory control Others : DKEFS verbal fluency, design fluency and tower achievement Grant & Chamberlain, 2020 17(11) 17(11) 24.62 32.63 HAM-D, HAM-A BED group reported subclinical levels of depression and anxiety. No further control BED group: agoraphobia (n = 2), social phobia (n = 1), cannabis use disorder (n = 1), antisocial personality disorder (n = 1) Cognitive Flexibility : IED (total errors, adjusted for stages not completed) Working Memory : One Touch Stockings of Cambridge task (problems solved on first choice), Spatial Working Memory Task* (total errors) Inhibition : SST (stop-signal reaction time) Others : CGT (quality of decision making) Kittel et al, 2017 22(18) 44(36) 14.99 85.66* BDI-II S-Diff in depression sym...…”
Section: Resultsmentioning
confidence: 99%
“…Six additional studies not included in the meta-analysis reported mixed findings. In three studies, there was no evidence of altered performance in the BED group compared to obese (18,37,41) or normal weight controls (18,33). In one study (56), individuals with BED showed poorer performance compared to normal weight controls on all indexes of the WCST, apart from perseverative errors.…”
Section: Perseverative Errors: Wcst Pcet and Iedmentioning
confidence: 91%
“…People with BED showed higher rates of decision-making impairments compared to normal weight controls in three studies. On the other hand, others reported no significant differences in this domain between BED and obese controls (36,37) and normal weight controls (33).…”
Section: Decision-makingmentioning
confidence: 96%
See 1 more Smart Citation
“…Such effects may be explained both neurobiological, psychosocial, and behavioral changes (Ashdown‐Franks et al, ; Lubans et al, ; Mullen & Hall, ). If physical activity is included in the treatment of BN and BED, such changes may be relevant to expect as both disorders are acknowledged as cognitive and neurobiological in nature (Donnelly et al, ; Grant & Chamberlain, ). Both immediate and longitudinal effects from moderate intensity physical activity have shown positive cognitive effect by improving eating behavior and self‐regulation in healthy students (Lowe, Hall, Vincent, & Luu, ; Oaten & Cheng, ).…”
Section: Introductionmentioning
confidence: 99%